Learning from the Mexican Experience with Taxes on Sugar-Sweetened Beverages and Energy-Dense Foods of Low Nutritional Value : Poverty and Social Impact Analysis - Bonilla-Chacin, Maria Eugenia; Iglesias, Roberto; Suaya, Agustina; Trezza, Claudia; Macías, Claudia (World Bank, Washington, DC, 2016)
Faced with a large and increasing obesity epidemic, the Mexican Government in the last years has increased efforts to prevent and control it. In October 2013, Mexico’s Congress passed legislation imposing taxes on sugar-sweetened beverages (SSBs) and calorie-dense foods of low nutritional value. These taxes were part of a comprehensive strategy to prevent and control obesity, overweight and diabetes. In addition to fiscal policy and regulation, this strategy included other health promotion and prevention interventions as well as measures to ensure better access to effective health care services. The decision to implement this fiscal policy was the result of a long advocacy process in which different actors participated, including civil society organizations and government agencies, which provided needed evidence on the status of the epidemic and options to fight against it. The taxes were designed to avoid, as much as possible, the substitution of consumption of the taxed goods for other unhealthy foods and beverages not subject to taxation. These taxes have been successful in increasing both the fiscal revenues and the price of the products taxed. There is also evidence that they have reduced consumption, particularly of SSBs. The taxes seem to have the highest impact among people in the poorest quintiles of the income distribution, who had experienced the highest increase in consumption of the goods under taxation in the last years. A debate remains on the actual impact of the taxes, particularly on health outcomes. Thus it is important to continue monitoring the impact of the taxes through the development of price and volume indicators, based on publicly available data, as well as health outcome indicators.